Allium fistulosum as a novel system to investigate mechanisms of freezing resistance. Issue 1 (21st November 2012) - Tanino, Karen K.; Kobayashi, Shion; Hyett, Craig; Hamilton, Kaila; Liu, Jun; Li, Bin; Borondics, Ferenc; Pedersen, Tor; Tse, John; Ellis, Tom; Kawamura, Yukio; Uemura, Matsuo
<x xml:space="preserve">Abstract</x> Allium fistulosum was investigated as a novel model system to examine the mechanism of freezing resistance in cold hardy plants. The 250 × 50 × 90 µm average cell size and single epidermal cell layer system allowed direct observation of endoplasmic reticulum (ER), functional group localization during acclimation, freezing and thawing on an individual cell basis in live intact tissues. Cells increased freezing resistance from an LT50 of −11°C (non‐acclimated) to −25°C under 2 weeks of cold acclimation. Samples were processed using Fourier transform infrared technology (FTIR) on a synchrotron light source and a focal plane array detector. In addition, confocal fluorescent microscopy combined with a cryostage using ER selective dye of ER‐Tracker allowed more detailed examination of membrane responses during freezing. Cold acclimation increased the ER volume per cell, and the freeze‐induced cell deformation stopped ER streaming and ER vesiculation subsequently occurred through the breakdown in the ER network. Freeze‐induced ER vesicles in cold‐acclimated cells were larger and more abundant than those in non‐acclimated cells. According to FTIR, the carbohydrate/ester fraction and α‐helical/β‐sheet secondary structure localized in the apoplast/plasma membrane region were most visibly increased during cold acclimation. Results suggest the mechanism of cold acclimation and freezing resistance in very hardy cells may be associated with both alterations in the apoplast/plasma membrane region and the ER cryodynamics. Allium fistulosum appears to be a useful system to obtain direct evidence at both intra and extracellular levels during cold acclimation and the freezing process.